Kaempferia parviflora extract and its methoxyflavones as potential anti-Alzheimer assessing in vitro, integrated computational approach, and in vivo impact on behaviour in scopolamine-induced amnesic mice - Pitchayakarn Takomthong; Pornthip Waiwut; Chavi Yenjai; Jinda Wangboonskul; Kusawadee Plekratoke; Puguh Novi Arsito; Carlo Ballatore; Chantana Boonyarat (PLoS ONE, 2025)
Alzheimer’s disease (AD), a growing global challenge, lacks effective preventive and therapeutic strategies. This study explored the promising potential of the Kaempferia parviflora (KP) and its methoxyflavones (MFs) against the disease. We evaluated KP extract and its five MFs for antioxidant capacity, cholinesterase inhibition (AChE, and BChE), amyloid plaque (Aβ) reduction, neuroprotection, and memory improvement in a mouse model. HPLC quantified the five MFs in KP extract, with 5,7-dimethoxyflavone (F1) being the most abundant. 5,7,4′-Trimethoxyflavone (F3) and 5-hydroxy-3,7-dimethoxyflavone (F4) exhibited the strongest AChE and BChE inhibitory activities, respectively. MFs hindered Aβ1-42 aggregation and destabilized fibrils, with F3 showing the potent anti-aggregation and the strongest fibril destabilization. They also protected SH-SY5Y cells from Aβ1-42-induced damage. Notably, F3 combined anti-cholinesterase and anti-Aβ activities, suggesting its potential as a multi-target agent. KP extract ameliorated scopolamine-induced memory deficits in mice, suggesting its potential for cognitive improvement. These findings revealed that KP can be a promising candidate for herbal medicine development against AD. Its multi-target MFs offered a unique advantage by targeting multiple AD pathways. KP may have a great potential to modify the disease and overcome the challenge of drug development as cognitive enhancing herbal medicine.